2020
DOI: 10.1101/2020.09.15.20157123
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative MRI susceptibility mapping reveals cortical signatures of changes in iron, calcium and zinc in malformations of cortical development in children with drug-resistant epilepsy

Abstract: Objective Malformations of cortical development (MCD), including focal cortical dysplasia (FCD), are the most common cause of drug-resistant focal epilepsy in children. Histopathological lesion characterisation demonstrates abnormal cell types and lamination, alterations in myelin (typically co-localised with iron), and sometimes calcification. Quantitative susceptibility mapping (QSM) is an emerging MRI technique that measures tissue magnetic susceptibility (χ) reflecting its mineral composition. We used QSM … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 82 publications
1
3
0
Order By: Relevance
“…Accordingly, in this study the detected alterations were not specific to (or driven by) the focal cortical lesions of patients, as demonstrated by the observed heterogeneity of qMRI profiles within the investigated FCDs. Interestingly, the detected heterogeneity of qMRI cortical signatures in patients’ lesions supports previous evidence that qMRI changes may be specific to different FCD subtypes (Lorio et al, 2020, 2021).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Accordingly, in this study the detected alterations were not specific to (or driven by) the focal cortical lesions of patients, as demonstrated by the observed heterogeneity of qMRI profiles within the investigated FCDs. Interestingly, the detected heterogeneity of qMRI cortical signatures in patients’ lesions supports previous evidence that qMRI changes may be specific to different FCD subtypes (Lorio et al, 2020, 2021).…”
Section: Discussionsupporting
confidence: 85%
“…Overall, our findings indicate the presence of widespread, depth-mediated qT1 and qT2 increases in a heterogeneous sample of children with focal epilepsy. Additionally, they demonstrate significant alterations in patients’ intracortical organization (Lorio et al, 2021), as shown by a “surface-out” gradient of increased qT1 and qT2 values driven from the WM/GM border in patients. Consistent with previous evidence (Ahmad et al, 2020; Bernhardt et al, 2018; Hattingen et al, 2018), the observed cortical changes were robust to potential confounders, including age-variation and differences in vertex-wise cortical thickness and curvature, suggesting that they represent a different underlying pathophysiological mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Error at any step is likely to be introduced, even propagated and accumulated in the following process. Researchers have proposed many algorithms for addressing the challenges in these steps over the past years, and these have been successfully applied to measure iron in brain tissue, distinguish between hemorrhage and calcification, measure the cerebral metabolic rate for oxygen and liver iron deposition, and reveal the cortical development in children with drugresistant epilepsy (3,(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%